Hello ;
<span>an = 1 • 3n - 1</span>
Answer:
a= 4
b= -10
c= -7
d= -1
Step-by-step explanation:
Answer:
The expression that is greater is a (b - c)
Step-by-step explanation:
- a < 0 and c > b, this means <u>(by the addition property)</u> that c - c > b - c⇒0 > b - c
so for the product <u>a(b - c) </u>we would have a multiplication of a negative number <em>a</em> and another negative number <em>(b - c)</em>. We know that the result of the <u>multiplication of two negative numbers is a positive number.</u>
Therefore, a (b - c) > 0
- a < 0 and c > b, this means <u>by the addition property</u> that c - b > b - b⇒ c - b > 0
so for <u>a(c - b)</u>, we have the negative number <em>a</em> multiplied by the positive number <em>(c - b). </em>We know that the result of the <u>multiplication of a negative number by a positive number is negative. </u>
<u>Therefore a (c - b) < 0</u>
Thus, the expression that is greater is the positive one which is a (b - c)
<span>2(8x - 4) = 32 distribute through parenthesis
16x - 8 =32 add 8 on both sides to isolate x
16x = 40 divide by 16 on both sides to isolate x
x= 40/16 simplify, Divide 40 by 16
x = 2.5 this is your final answer, I hope it helps!</span>